Estimation of Probability Density Function of a Random Variable for Small Samples - Srinivasan, V.S. (Defence Science Journal, 2004)
A theoretical method of estimating the most general form of probability density functions of random variables has been described. The estimated probability density function depends on the mean value of exponential dimrbut~ono f the lnlt~arla ndom variable. By the most general form of the probability density function, it is meant that the survivor functions are of exp (-A P) or exp (-y P ) or combinations of these functions for different values of h and y.